Pemberdayaan Wanita Usia Subur dalam Deteksi Dini Kanker Payudara Melalui BSE - Yuni Astuti; Tuti Anggarawati; Erni Suprapti (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Breast cancer is a malignant tumor that develops from breast cells that grow and develop uncontrollably. These cells divide faster than normal cells, accumulate into clusters or masses, and spread to other parts of the body. The high prevalence rate and low public knowledge about breast cancer cause many cases to be found at an advanced stage. Cancer cases that are found early and receive fast and appropriate treatment will provide healing and a longer life expectancy. Prevention efforts are made to increase public awareness in recognizing the symptoms and risks of cancer so that they can determine the right prevention and early detection steps. One of the simplest and cheapest ways is to conduct early detection through Breast Self Examination (BSE). The results of this activity are an increase in knowledge about early detection as an effort to prevent breast cancer through BSE after education is carried out